Batik jati Lestari Kabupaten Blora: Kultural Ekonomi - Putra, Firmansyah (Jurnal Industri Kreatif dan Inovatif, 2025)
This study examines the role of Batik Jati Lestari as a representation of the local culture and identity of Blora Regency and its impact on the economic recovery of artisans after the COVID-19 pandemic. Using a qualitative approach and Stuart Hall's cultural representation theory, primary data was obtained through in-depth interviews, participant observation, and documentation. The results show that the establishment of Batik Jati Lestari as the official uniform of the State Civil Apparatus (ASN) since 2023 has increased demand for local batik and revitalized the batik MSME sector impacted by the pandemic. There is a need to increase socialization and education regarding the philosophical meaning of motifs so that the process of cultural representation runs effectively and the meaning of batik can be internalized by the wider community. Inclusive and participatory government policies are key to strengthening cultural identity while supporting the empowerment of the creative economy in Blora. This study provides strategic recommendations for the development of batik as a cultural symbol and driver of the local economy.